THE SOCIAL NATURE OF THE VALUES AND PROBLEMS OF ORGANIZATION AND INTERNALIZATION OF VALUES AND VALUE ORIENTATION IN PERSONALITY STRUCTURE - A. Kravets; A. Utyuganov (Вестник университета)
The article is devoted to the problems of values and value orientations. We consider the duality of values - individual and social, at the kind of values. These issues are considered from the perspective of different scientific theories.